Exploring learning communities’ actions and perceived impact on healthy weight approaches across Dutch municipalities - M. J.J. ter Bogt; K. E. Bevelander; G. R.M. Molleman; M. E.T.C. van den Muijsenbergh; G. A.J. Fransen (BMC Public Health)
Abstract Introduction Various Dutch municipalities apply healthy weight approaches (HWAs) to reduce overweight and obesity rates. Systems science theory suggests that HWA effectiveness may be increased by targeting leverage point themes (LPT) that drive change across HWAs. Actions relating to these LPTs can be applied by learning community (LC) members on different system levels varying from superficial to deep. However, there is a knowledge gap about how LCs can contribute to system changes and about LC members’ perception of their impact. Therefore, this study aims to gain insights into the perceived impact of these LCs on HWAs. Methods This two-step study was performed in relation to two LCs and a steering committee executing actions over a 2.5-year period. At meetings, LCs created action lists (n = 8 and n = 2, respectively). We analyzed these action lists by identifying the corresponding LPTs, system levels, and perceived successful execution for each action, subsequently running frequencies and regression analyses. Additionally, we thematically analyzed qualitative evaluation questionnaires completed by LC members and the results of semi-structured interviews that we conducted with members. Results Actions targeted all system levels and most LPTs at least once, including ten themes newly identified in this study. Actions that targeted the most superficial system level were most likely to occur. Knowledge exchange and combined forces LPTs were targeted the most. The communication strategies LPT was less likely to be executed successfully. Throughout later LC meetings, more actions were formulated regarding combined forces and central players LPTs, at the most superficial system level. Furthermore, members perceived impact on three main themes: ideas about the next steps toward solutions, more collaboration, and working more effectively. Discussion Multidisciplinary LCs can contribute to creating new ideas and collaborations and to applying actions for a local HWA across most LPTs and system levels. These insights can be used during LC meetings to continuously adjust LCs and HWA actions when necessary. Future research is needed, for instance to gain further insights into new topics, the desired number of actions per LPT, and long-term LC impacts.